Recent Italian Events on BIM (diségno, 2017)
In the last few years, several important events related to BIM have taken place in Italy. As known, BIM is the acronym of Building Information Modeling, a work system for structuring information during the process of building design. Professional associa- tions as well as the academic world have been exploring its potentialities, with an aim to upgrading study pro- grams, or as a new field of work to be developed in scientific research.